A Phase 1 Study to Assess the Pharmacokinetics, Food Effect, Safety, and Tolerability of Sepiapterin in Healthy Japanese and Non-Japanese Participants - Lan Gao; Diksha Kaushik; Kimberly Ingalls; Neil Smith; Ronald Kong (MDPI AG, 2024)
Background: Sepiapterin is a natural precursor of tetrahydrobiopterin (BH4), a key cofactor for phenylalanine hydroxylase. It is being developed for the treatment of patients with phenylketonuria. In this study, the ethnic differences in pharmacokinetics and safety of sepiapterin in Japanese and non-Japanese participants and food effects were evaluated. Methods: Healthy participants (n = 60) received a single oral dose of sepiapterin at either 20, 40, or 60 mg/kg with a low-fat diet. The Japanese participants received two doses at 40 mg/kg, either under fasted conditions or with a low-fat diet with a 3-day washout period in between. Results: Sepiapterin was well tolerated in all participants, with no serious adverse events. Sepiapterin was quickly absorbed (Tmax 1.4-4.5 h) and rapidly and extensively converted to BH4 (Tmax ~4 h). Exposures to sepiapterin were <1% of BH4. BH4 exposures were essentially dose-independent between 20 and 60 mg/kg. A low-fat diet increased BH4 exposures in Japanese participants by 1.7-fold compared with fasted conditions. Conclusions: BH4 exposures (Cmax and AUC0-last) in Japanese participants were 10-30% higher than in non-Japanese participants, which is deemed not clinically relevant; no dose adjustment is warranted. The slightly higher BH4 exposures in Japanese participants are likely due to the higher frequency of ABCG2 c.421C>A mutation in the Japanese population.